Analysis management and referral process for victims of violence in house ladder in first level health services - Rosida, Luluk; Putri, Intan Mutiara (Universitas 'Aisyiyah Yogyakarta, 2025)
The health impacts experienced by victims of domestic violence, especially women, are quite widely reported. From the results of research obtained in the United States, as many as 37% of women who experienced violence from perpetrators and underwent examinations at health services ended up in hospitalisation in emergency services. The purpose of this study is to analyse the Management and Referral Process of Victims of Domestic Violence (Case Study at first-level health services). The research method employed is descriptive research, specifically analysing primary data to describe the violence that existed over 3 years. The research location was at one of the first-level health services (community health centres) in Bantul Regency. The results showed that the characteristics of victims of domestic violence based on gender were mostly experienced by women, as many as 15 people (78.9%), and men, as many as 4 people (21.1%). Based on interviews with officers, the management provided ranged from first aid for injuries to counselling by community health centre officers or a referral process for serious injuries. However, most victims did not want to continue reporting to the authorities or the legal realm. And most victims reported that they would resolve the matter internally within their respective families. The findings of this research contribute to describing the management and referral process for victims of domestic violence to primary health care.